Some Liver Enzymes And Biomarkers Of Rabbits Fed On Groundnuts Grown In Kutchalli Waste-Pit Materials (Borno State) Nigeria. - OSADOLOR; B.HUMPHREY; NWANZE.A.C.EMMANUEL; ANOLIEFO, G.OBI (International Journal of Pharma and Bio Sciences, 2010)
Kutchalli drilling waste-pit materials (kwpm) in Nigerian National Petroleum Corporation (NNPC) exploration sites in Borno State were evaluated for systemic toxicity to inhabitants (man, animasl and plants) via food chain. The biochemical parameters used to assess the liver (AST, ALT, AP, TB, CB, TP and Alb) of the laboratory rabbits were evaluated at intervals for 14 weeks using standard procedures.Results revealed disparity in the parameters in the control animals when compared with those fed with groundnut produced in kwpm (AST 12±0.6, ALT 12±0.5, ALK phos 26±2.0, TB 0.8±0.2, DB 0.6±0.2, TP 6.1±0.8, alb 3.4±0.5 and Glb 2.7±0.4 for control rabbits and (AST 36±2.0, ALT 25±2.2, Alk.phos 38±1.2, TB 2.9±0.4, DB 2.5±0.4, TP 5.6±1.1, Alb2.8±1.0 and Glb 2.8±0.t) It was significant at P<0.05. In the first one week, the parameters evaluated except TP, Alb and Glb were significantly elevated compared to the control P<0.05 in the following weeks 4, 8 and 14 in the groups (5 and 7). The livers of rabbits fed with groundnuts grown in kwpm showed abnormal patterns of liver biochemical parameters investigated in this Kutchalli area of Borno State, where this research was carried out. The inhabitants are mainly farmers, fishers and cattle rearers due to green vegetation. Therefore, there is need for proper waste disposal system probably via bioremediation to avoid harmful carry over to the generation of the inhabitants yet unborn.